Analysis of the complete mitochondrial genome sequence of Palinura homarus. Issue 1 (1st January 2017) - Xiao, Bao-hua; Zhang, Wuchai; Yao, Wei; Liu, Chu-wu; Liu, Li
Abstract: The complete mitochondrial genome sequence of Palinura homarus was obtained using PCR amplification and walking sequencing (GenBank accession no. JN_542716). The complete mitochondrial genome of P. homarus was 15, 665 bp long and showed significant AT bias (67% AT content, 33% GC content). The A + T-rich region included copy-related control information and a poly (dT) structure that related to replication and transcription. In this study, the gene arrangement was consistent with other Palinura mitochondrial genomes and the sequence was strikingly similar to Panulirus ornatus, which would be useful in species identification and natural resources conservation.